2013
DOI: 10.1186/1687-6180-2013-23
|View full text |Cite
|
Sign up to set email alerts
|

Multi-GPU based on multicriteria optimization for motion estimation system

Abstract: Graphics processor units (GPUs) offer high performance and power efficiency for a large number of data-parallel applications. Previous research has shown that a GPU-based version of a neuromorphic motion estimation algorithm can achieve a ×32 speedup using these devices. However, the memory consumption creates a bottleneck due to the expansive tree of signal processing operations performed. In the present contribution, an improvement in memory reduction was carried out, which limited accelerator viability usag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…This shortcoming seriously hampers the practical application of this technology as an help for diagnostic which could be done by dermatologists or even general practitioners. Fortunately, previous researches have shown that GA-based designs can be optimized via different parallel computing environments [2,13,14,36]. For KMGA, the huge quantity of data from multispectral images processing and GA's population information results in a bottleneck of memory consumption on GPUs and FPGAs, while multi-core CPUs have better overall properties, specially for efficiency and robustness performances.…”
Section: Introductionmentioning
confidence: 99%
“…This shortcoming seriously hampers the practical application of this technology as an help for diagnostic which could be done by dermatologists or even general practitioners. Fortunately, previous researches have shown that GA-based designs can be optimized via different parallel computing environments [2,13,14,36]. For KMGA, the huge quantity of data from multispectral images processing and GA's population information results in a bottleneck of memory consumption on GPUs and FPGAs, while multi-core CPUs have better overall properties, specially for efficiency and robustness performances.…”
Section: Introductionmentioning
confidence: 99%
“…Other approaches to reducing the search parameter space include techniques like genetic algorithms (Garcia et al 2013), simulated annealing, or even a simple random search, which has been shown to be surprisingly effective in studies of dense computational codes on CPUs (Seymour et al 2008). The savings can be dramatic: a study by Ganapathi et al (2009) that used machine learning techniques to reduce a parameter search space yielded a speed-up of 2000× over the full search, while achieving tuning results comparable to a human expert.…”
Section: Autotuningmentioning
confidence: 99%
“…There are several previous works regarding motion estimation hardware acceleration [9][10][11] and, specifically, block-matching algorithms [12], though none of them explore the custom instruction paradigm. Looking into block-matching techniques, three frequently used techniques can be classified: the full-search technique (FST) [4], the three-step-search technique (TSST) [13], and the two-dimensional logarithmic-search technique (2DLOG) [14].…”
Section: Introductionmentioning
confidence: 99%